Ahl Al-Sunnah Wa Al-Jamā‘Ah A Semantic Analysis - Baharuddin Abd Rahman (Sekolah Tinggi Agama Islam Indonesia Jakarta, 2021)
Understanding about the meaning of “Ahl al-Sunnah wa al-Jamā‘ah” in the hadith which reads: